Pengaruh Peraga Multimedia Huruf Terhadap Kemampuan Meniru Huruf Anak Usia 4-5 Tahun - dwi rahayu, puji; Seh Turuy; Syifa Jalaluddin (Universitas Muhammadiyah Metro, 2025)
The ability of 4-5 year olds to imitate letters varies; most children cannot yet correctly imitate letters, and they still make mistakes in identifying, naming, pointing to, and writing letter shapes. The purpose of this study is to determine the effect of multimedia letter aids on the ability to write letters A-Z in children aged 4-5 years, and to determine the effect of multimedia letter aids on the ability to pronounce letters A-Z in children aged 4-5 years at Al-Khairat Kalumpang Kindergarten, Ternate City. The research method used is experimental research with a quantitative approach. The research design is a pre-experimental design with a one-group pretest-posttest design combined with a one-shot case study design. The results of this study on letter writing ability data show a calculated t-value of 6.896 > a table t-value of 2.13145. Therefore, based on the decision-making process above, it can be concluded that Ho is rejected and Ha is accepted. For letter pronunciation ability data, the calculated t-value is 8.857 > the table t-value of 2.13145. Therefore, based on the decision-making process above, it can be concluded that Ho is rejected and Ha is accepted. Therefore, it can be concluded that there is a difference in the average between pre-test and post-test letter writing and speaking abilities, meaning that there is an effect of letter multimedia aids on the letter writing and speaking abilities of 4-5 year old children. Based on the results, it can be concluded that there is a significant improvement in the ability to imitate (write and speak) letters in 4-5 year old children after being given treatment in the form of letter multimedia aids. This finding can serve as a reference for educational institutions, parents of young children, and the community, as well as policymakers, in providing multimedia letter displays to stimulate children's letter imitation skills.